Magnetically assisted quantum cascade laser emitting from 740 GHz to 1.4 THz - Scalari, G; Turcinkova, D; Lloyd-Hughes, J; Amanti, M; Fischer, M; Beck, M; Faist, J (2010)
In this paper we show that by applying a perpendicular magnetic field to a quantum cascade structure it is possible to enhance the gain of different optical transitions. The combination of magnetic confinement with a broadband, cutoff-free optical resonator allows the demonstration of laser action over a large bandwidth, from 733 GHz to 1.38 THz together with the emission at 3.2 THz. A different lasing scheme is revealed that does not rely on resonant tunneling as the main injection mechanism. In combination with the magnetically enhanced gain laser emission at 1 THz is observed up to a temperature of 115 K, which corresponds to a ratio kB T/hv=2.3 between the lattice thermal energy and the laser photon energy. © 2010 American Institute of Physics.